A global perspective on central bank digital currency. Issue 1 (2nd January 2021) - Lee, David Kuo Chuen; Yan, Li; Wang, Yu
ABSTRACT: This paper discusses the key considerations of CBDC design to balance benefits and risks and presents best practices in CBDC design from a global perspective. Using China's CBDC as an illustration, this paper discusses two-tier or multi-tier ledger design and proposes ten enablers of mass adoption and successful implementation. This proposed design allows central banks to manage the process flow, focus on the monitoring and control, without bearing all the load or exposing to over-centralized risks. It concludes that CBDC will be the primary tool in the future digital economy, and countries that are conversant with the technology will have a competitive advantage. Learning from the implementation, continuously reviewing the existing regulation, and improvising whenever international dynamics change the landscape are vital attributes of a successful implementation.